Dielectric flow sensing in resin transfer moulding of carbon fibre reinforced composites. - Skordos, Alexandros A.; Partridge, Ivana K. (Maney Publishing, 2000)
An in situ dielectric technique for sensing flow is outlined and shown to be suitable for use in moulding of composites from liquid resins containing continuous conducting fibres. This work builds upon the recent development of a sensor for monitoring flow and cure in thermosetting composites with (non- conductive) glass reinforcements. The linear relationship between the position of the flow front in the mould and the electrical admittance of the sensor system, which is observed in resins with non-conductive reinforcements, was found to extend to resins containing conducting fibres. The performance of the sensor in detecting the position of the flow front was evaluated by comparison with visual observations. The capability of the sensing system to monitor the cure of the resin after mould filling was also investigated. The results demonstrate that the sensor can both locate the flow front accurately and monitor the cure, identifying vitrification in a way that is similar to conventional microdielectrometry. Data from flow measurements are output in complex number format, which offers the potential to produce a method that can be used to evaluate the performance of the sensor system quantitatively.